FRI0629-HPR Back To Action: A Guide To Exercising Safely in The Gym with Ankylosing Spondylitis - Book and App User Perspectives. (15th July 2016) - Hamilton, J.; Garces Bovett, C.; Harris, C.; Jeffries, C.; Jones, T.
Abstract : Background: Back to Action ( B2A ) is a guide designed to help people with ankylosing spondylitis and axial spondyloarthritis (AS) exercise safely in the gym, produced by NASS in association with the Defence Medical Rehabilitation Centre at Headley Court. It was first published in print in 2010, and was published as a free iOS app in 2011 and in Android format in 2012. Two surveys were conducted from 1 November 2014 to 30 April 2015 to gather information on user satisfaction with the B2A book and app, and their impact on users. Key findings included; the structure and content of B2A was highly regarded, 67% now exercise more at home than previously, and 95% of respondents would recommend the guide to others with AS. Objectives: The information and comments collected will help to shape the next phase of B2A 's development as well as help to review the current versions of the book and app to ensure that the needs of the user are met fully. Methods: One survey dealt with the printed version of B2A, the other with the app. Apart from questions relating to format-specific topics, both surveys contained the same 17 questions designed to elicit both numerical ratings and qualitative comments, and were advertised via the NASS website, Facebook and Twitter. Additionally, the apps survey was sent to all users via a push notification update. The answers to both surveys were analysed together. Results: Two hundred and five people completed the surveys. Sixty-five percent were in the 25–44 age range. Each section of B2A received an average rating of 4.10 or above out of a possible 5 for excellence, with the guide overall receiving an average rating of 4.23 out of 5. Ninety-five percent of those surveyed would recommend B2A to someone with AS. In terms of measuring B2A 's impact, 67% said that they exercise more at home since buying or downloading the guide. When asked to rate how significantly the guide has improved their general fitness (where 5 is very significantly), the average rating was 3.50. The average rating was 3.20 when respondents were asked to rate how significantly B2A had improved their AS. Suggestions for future development of B2A showed a strong desire for sections on the use of free weights (53%) and gym balls (33%). Other respondents asked for walking and cycling tips, and stretches for the swimming pool. Conclusions: Although the structure and content of B2A were rated high, the impact of the guide on respondents' general fitness and AS symptoms did not rate as correspondingly high. However, the material never formally addressed how to measure general fitness and therefore the potential variability in interrupting this may explain the low score. More successfully, B2A seems to have had an effect on the numbers of users now exercising more at home, as well as encouraging others to join gyms, crucial to the management of AS. Compliance in exercising at home is low amongst people with AS despite awareness of the benefits of exercise [i] and so the book and app were successful in this area. Various areas for future development were also identified, which should increase the scope and impact of subsequent editions. References: [i]Physical Activity and Exercise: Perspectives of Adults With Ankylosing Spondylitis, O'Dwyer T, McGowan E, O'Shea F, Wilson F, Journal of Physical Activity & Health, 28 October 2015 Disclosure of Interest: None declared